Deteksi Perubahan Garis Pantai Menggunakan Citra Synthetic Aperture Radar (SAR) di Pesisir Tenggara Bali (Kabupaten Gianyar dan Klungkung) - Kadek Dwi Artama; I Wayan Gede Astawa Karang; I Nyoman Giri Putra (Fakultas Kelautan dan Perikanan Universitas Udayana, 2019)
Coastline change is a phenomenon caused by sediment decrease or increase in the coastal area that occurs continuously. This phenomenon is caused by abrasion, erosion, and accretion. Bali is one of the provinces that have coastal with quite noticeable conditions, which is the southeast coast of Bali, the coast of Gianyar and Klungkung Regencies. Identification of coastline changes is important to determine policies that can be taken to maintain coastal balance. Remote sensing is one way to identify coastline change. In this study, the image used is SAR images of ALOS PALSAR and Sentinel-1 satellites with a resolution of 10 meters to extract the coastlines of Gianyar and Klungkung in 2007 and 2018. Method used for shoreline extraction is Image Threshold pproach. Coastline changes analysis in this study used the Digital Shoreline Analysis System (DSAS) application. Analysis results of coastline changes in Gianyar and Klungkung for 11 years in range shown the highest erosion and accretion occurred in the Klungkung coastal with erosion area reached 168,142.05 m2, and the accretion area reached 207,531.2 m2. Coastal change in Gianyar Regency caused by erosion reached 124,930.5 m2, and the accretion area reached 85,123.86 m2. The highest change rate in Gianyar occurred in Saba village at the rate of 2.63 m/year in erosion, whereas in Klungkung it occurred in Gunaksa village reaching 13.25 m/year in accretion.